2020
DOI: 10.21203/rs.3.rs-71427/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genotypic and genetic diversity of enset (Ensete ventricosum) landraces used in traditional medicine is similar to the diversity found in starchy landraces

Abstract: Background Enset (Ensete ventricosum) is a multipurpose crop extensively cultivated in southern and southwestern Ethiopia for human food, animal feed and fiber. It contributes to the food security and rural livelihoods of 20 million people. Several distinct enset landraces are cultivated for their uses in traditional medicine. Socio-economic changes and the loss of indigenous knowledge might lead to the decline of important medicinal landraces and their associated genetic diversity. However, it is currently u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Gardon et al [50] showed high degree of variability among M. sativa genotypes with six SSR markers. Cholastova and Knotova [30] demonstrated that the estimation of genetic diversity of Medicago genotypes could be obtained even with only three SSR markers. Based on obtained results, used SSR markers were as efficient to determine genetic variation among the studied M. tunetana accessions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gardon et al [50] showed high degree of variability among M. sativa genotypes with six SSR markers. Cholastova and Knotova [30] demonstrated that the estimation of genetic diversity of Medicago genotypes could be obtained even with only three SSR markers. Based on obtained results, used SSR markers were as efficient to determine genetic variation among the studied M. tunetana accessions.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers are complementary to morphological and biochemical markers [22]. Several studies have been realized on the genetic diversity of Medicago genotypes using different markers such as AFLP [23,24], RAPD [25,26], RFLP [27,28] and SSR [29][30][31][32]. The microsatellites as polymorphic DNA markers have been widely employed in molecular studies thanks to their facility and efficiency for population genetic analysis [33][34][35] while, using SSR markers for genetic variability within perennial Medicago genotypes had not been very developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation